Penerapan Model Pembelajaran Kooperatif Tipe Student Teams Achievement Divisions Dengan Menggunakan Aplikasi Statistical Product And Service Solutions Untuk Meningkatkan Hasil Belajar Mahasiswa Pada Mata Kuliah Statistik Pendidikan - Sri Irawati (Institut Studi Islam Muhammadiyah (ISIMU) Pacitan, 2017)
The purpose of this study is to describe the activities, student’s achievment, and their responese toward Student Teams Achievement Divisions (STAD), as cooperative learning by using Statistical Product And Service Solution (SPSS) in educational statistic class. This research is Classroom Action Research (CAR). There are four steps were done in this classroom action reseach, they are planning, action, observation, and reflection. The subject of this study is the 6th semester students in 2015/2016 academic year, who are taking statistics class in Islamic Education as their majority in STAI Nazhatut Thullab Sampang. Data collection technique was done by observation, questionnaire, and test. Observation was done in order to find out the students’ activities during the class, while questionnaire was used to understand the students’ response toward STAD teaching and learning with SPSS. Test was done to value the students’ achievement. The result of this study based on the observation in cycle 1 showed the average of students’ activities in class was 69.3%, categorized as Active Enough. The average in cycle 2 was 74.6%, categorized as Active. For the test, the average was 73.5 in cycle 1 and 87.6 in cycle 2. While the classical student’s completeness increases from 70% to 83% In the case of students’ response toward the SPSS use, the writer found the students’ average in cycle 1 was 76.3 and 89.5 in cycle 2, where both of them were in positive categories. The writer can conclude that Student Team Achievement Division (STAD) with SPSS as a kind of cooperative learning, can improve students’ achievement.